2009
DOI: 10.2165/0044011-200929020-00002
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Fluticasone Furoate Nasal Spray Once Daily in Paediatric Patients Aged 6–11 Years with Allergic Rhinitis

Abstract: FFNS has a favourable safety and tolerability profile in patients aged 6-11 years with PAR or SAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 15 publications
2
38
0
Order By: Relevance
“…Fortunately, no clinically significant steroid adverse effects have been discovered in studies in children. [89][90][91][92][93][94][95][96] Saline Irrigation…”
Section: Intranasal Steroidsmentioning
confidence: 99%
“…Fortunately, no clinically significant steroid adverse effects have been discovered in studies in children. [89][90][91][92][93][94][95][96] Saline Irrigation…”
Section: Intranasal Steroidsmentioning
confidence: 99%
“…The recent Cochrane review (92) failed to find evidence supporting the effectiveness of intranasal corticosteroids but it excluded all the recent high-quality randomized controlled trials as they allowed rescue medication. Several studies have shown that the effects of mometasone, fluticasone and ciclesonide commence within a day of starting therapy (93). Intranasal corticosteroids probably also improve coexisting asthma (94-96) (A), and fluticasone furoate and mometasone may be effective for conjunctivitis (77,82,97) …”
Section: Intranasal Corticosteroidsmentioning
confidence: 99%
“…Of these 19 included studies, 9 reported data outcome on IOP (3,6,11,13,(20)(21)(22)(23)(24) , 1 on lens opacity (25) , and 9 studies reported data on both IOP and lens opacity (14,(26)(27)(28)(29)(30)(31)(32)(33) . This then left 18 (94.7%) (3,6,11,13,14,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) studies on IOP, and 10 (55.6%) (14,(25)(26)(27)(28)(29)(30)(31)(32)(33) ) on lens opacity in clearly defined patient groups that could be used for comparison in this systematic review (14,...…”
Section: Included Studiesmentioning
confidence: 99%
“…This then left 18 (94.7%) (3,6,11,13,14,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) studies on IOP, and 10 (55.6%) (14,(25)(26)(27)(28)(29)(30)(31)(32)(33) ) on lens opacity in clearly defined patient groups that could be used for comparison in this systematic review (14,(26)(27)(28)(29)(30)(31)(32)(33) . The study characteristics of the 19 included manuscripts are described in Tables 4 and 5.…”
Section: Included Studiesmentioning
confidence: 99%